2012
DOI: 10.1155/2012/614120
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of HIV Transcriptional Regulation and Their Contribution to Latency

Abstract: Long-lived latent HIV-infected cells lead to the rebound of virus replication following antiretroviral treatment interruption and present a major barrier to eliminating HIV infection. These latent reservoirs, which include quiescent memory T cells and tissue-resident macrophages, represent a subset of cells with decreased or inactive proviral transcription. HIV proviral transcription is regulated at multiple levels including transcription initiation, polymerase recruitment, transcription elongation, and chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 166 publications
0
51
0
Order By: Relevance
“…Two of the eight trials also conducted resistance exercise training, which included upper and lower extremity exercises such as bench press, leg press, knee extension, shoulder abduction, and arm curls. Two of the studies were led by a nurse investigator (Baigis et al, 2002;Smith et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two of the eight trials also conducted resistance exercise training, which included upper and lower extremity exercises such as bench press, leg press, knee extension, shoulder abduction, and arm curls. Two of the studies were led by a nurse investigator (Baigis et al, 2002;Smith et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that moderate-to high-intensity aerobic exercise conducted 2-3 times per week may have a signifi cant impact on increased maximum oxygen consumption (VO 2max ) in PLWH (Dolan et al, 2006;Hand et al, 2008;. Other benefi ts of exercise documented in apparently healthy adults and PLWH may include an increased plasma volume, increased cardiac output, decreased body mass index (BMI), subcutaneous fat, and abdominal girth (Cade, Peralta, & Keyser, 2004;McArdle, Katch, & Katch, 2010;Smith et al, 2001). Thoni and colleagues (2002) reported signifi cant decreases in total abdominal adipose tissue, total cholesterol, and triglycerides, and signifi cant increases in HDL cholesterol.…”
Section: Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…The HIV-1 LTR promoter plays an essential role in driving viral transcription and productive infection (22)(23)(24). To determine the mechanism of Naf1 inhibition of HIV-1 replication, we investigated whether Naf1 could inhibit LTR activity.…”
Section: Naf1 Suppresses Hiv-1 Long Terminal Repeat (Ltr)-driven Genementioning
confidence: 99%